Profile of pregnant women using delivery hut services of the Ballabgarh Health and Demographic Surveillance System in rural north India. Issue 2 (August 2016) - Kant, Shashi; Haldar, Partha; Singh, Arvind K.; Archana, S.; Misra, Puneet; Rai, Sanjay
Abstract: Objective: To describe women who attended two delivery huts in rural Haryana, India. Methods: The present observational study assessed routinely collected service provision data from two delivery huts located at primary health centers in the district of Faridabad. Data on sociodemographic characteristics, prenatal care, use of free transport services, and maternal and neonatal indicators at delivery were assessed for all pregnant women who used the delivery hut services from January 2012 to June 2014. Results: During the study period, 1796 deliveries occurred at the delivery huts. The mean age of the mothers was 23.3 ± 3.3 years (95% confidence interval 23.1–23.5). Of 1648 mothers for whom data were available, 1039 (63.0%) had travelled less than 5 km to the delivery hut. The proportion of mothers who belonged to a lower caste increased from 31.0% (193/622) in 2012 to 41.1% (162/394) in 2014. The proportion of mothers who were illiterate also increased, from 8.1% (53/651) in 2012 to 26.4% (104/394) in 2014. Conclusion: Belonging to a disadvantaged social group (in terms of caste or education) was not an obstacle to use of delivery hut services. The delivery huts might have satisfied some unmet needs of community members in rural India.